2004
DOI: 10.1016/j.ejogrb.2004.01.033
|View full text |Cite
|
Sign up to set email alerts
|

GnRH antagonists

Abstract: Ovarian stimulation is an important step in the success rate of in vitro fertilization (IVF) allowing multiple follicular growth, several oocytes and consequently more embryos. The combination of GnRH-antagonists (GnRH-ant) and gonadotrophins is now available for clinical use and represent a valid alternative to classical protocol with GnRH agonist. GnRH-antagonists induce a direct block of GnRH receptor with a rapid decrease in LH and FSH, preventing LH surge. Two protocols has been designed for assisted repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 57 publications
0
41
0
1
Order By: Relevance
“…GnRH agonists are initiated in the luteal phase and cause an initial stimulatory effect before acting to down-regulate the GnRH receptors prior to gonadotropin stimulation, and are associated with hypoestrogenic side effects and greater gonadotropin stimulation requirements (23). In comparison, GnRH antagonists act by competitive blockade of pituitary GnRH receptors and cause rapid suppression of FSH and LH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GnRH agonists are initiated in the luteal phase and cause an initial stimulatory effect before acting to down-regulate the GnRH receptors prior to gonadotropin stimulation, and are associated with hypoestrogenic side effects and greater gonadotropin stimulation requirements (23). In comparison, GnRH antagonists act by competitive blockade of pituitary GnRH receptors and cause rapid suppression of FSH and LH.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, GnRH antagonists act by competitive blockade of pituitary GnRH receptors and cause rapid suppression of FSH and LH. The advantages of GnRH antagonists include a rapid dose-dependent effect, the lack of an initial stimulatory effect, shorter duration of treatment with fewer symptoms of estrogen deprivation, a decrease in gonadotropin requirement for stimulation, and lower risk of developing severe ovarian hyperstimulation syndrome (18,19,(21)(22)(23)(24)27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequence of GnRH was characterized in 1971 by Schally et al (1971) with crucial functions associated with precise sequence. The 1, 2, 3, 6, and 10 positions were found to be vital for GnRH function, with positions 2 and 3 mediating gonadotropin release and positions 1 and 6 responsible for three-dimensional structure (Coccia et al, 2004). GnRH analogs were synthesized by substituting other amino acid bases or complex molecules at the 6 (Gly) and/or the 10 (Gly) positions (Fig.…”
Section: Gonadotropin-releasing Hormone Agonistsmentioning
confidence: 99%
“…In women, competitive blockage of GnRH-R by antagonist administration leads to significant falls in basal plasma LH, and to a lesser extent in FSH secretion (Coccia et al, 2004) but the same effect was not observed in the koala. The results of the current study demonstrates that the GnRH antagonist azaline B does not suppress basal LH or oestradiol-17β concentrations in the koala, however, it does appear to suppress the ability of anterior pituitary to respond to an exogenous GnRH challenge; prolonged treatment (10d) also successfully disrupts folliculogenesis, delaying the return to oestrus.…”
Section: Discussionmentioning
confidence: 91%
“…The successful ability of GnRH antagonists to reversibly block GnRH receptors in humans has lead to its inclusion in several assisted reproductive treatment schedules (Coccia et al, 2004). In women, competitive blockage of GnRH-R by antagonist administration leads to significant falls in basal plasma LH, and to a lesser extent in FSH secretion (Coccia et al, 2004) but the same effect was not observed in the koala.…”
Section: Discussionmentioning
confidence: 99%